IMPLEMENTASI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) SEBAGAI UPAYA PERCEPATAN PENDAFTARAN TANAH DI PROVINSI JAWA TIMUR - Jhon Dearson Parapat; Badrudin Kurniawan (Universitas Negeri Surabaya, 2021)
One of the important indicators to support the success of national development is the issue of restructuring. To minimize land conflicts, one of the efforts made by the government in this case is the Ministry of ATR or BPN to issue a program, namely Complete Systematic Land Registration (PTSL) with the aim of issuing certificates on land parcels as proof of ownership of a land parcel. In this study, researchers aimed to determine how the implementation of the PTSL program as an effort to accelerate land certificate registration in East Java Province, especially Jember Regency, Jombang Regency, Kediri Regency, Sidoarjo Regency, and Tulungagung Regency. Researchers used literature study research methods using library sources as the main data in the study. According to Van Meter and Van Horn (1975) there are 6 variables that influence the success of policy implementation, namely (1) policy standards and objectives; (2) resources; (3) relationships between organizations; (4) the characteristics of the executing agent; (5) implementor disposition; (6) social, economic, political conditions. The results of this study are based on the 6 indicators above, that the PTSL program in East Java Province has been running quite well, but there are still several obstacles such as a lack of understanding of the community, village officials and community groups related to the importance of land registration and problems related to administrative requirements to participate in the program. PTSL, as well as related to PPh and BPHTB issues whose value is too large for some people. Suggestions that can be given by researchers are to improve coordination between BPN and parties involved in implementing the PTSL program, and conduct regular outreach to the community, village officials, and community groups regarding the importance of the PTSL program, provide training related to instructions and technical implementation of the PTSL program..Keywords: National Development, Implementation, Systematic Land Registration. Salah satu indokator penting penunjang keberhasilan pembangunan nasional ialah masalah peratahan. Untuk meminimalisir konflik pertanahan, salah satu upaya yang dilakukan oleh pemerintah dalam hal ini adalah Kementrian ATR atau BPN mengeluarkan suatu program yaitu Pendaftaran Tanah Sistematis Lengkap (PTSL) dengan tujuan penerbitan sertifikat pada bidang tanah sebagai tanda bukti kepemilikan atas suatu bidang tanah. Dalam penelitian ini, peneliti bertujuan untuk mengetahui bagaimana implementasi program PTSL sebagai upaya percepatan pendaftaran sertifikat tanah di Provinsi Jawa Timur, terutama Kabupaten Jember, Kabupaten Jombang, Kabupaten Kediri, Kabupaten Sidoarjo, dan Kabupaten Tulungagung. Peneliti menggunakan metode penelitian studi kepustakaan dengan menggunakan sumber-sumber pustaka sebagai data utama dalam penelitian. Menurut Van Meter dan Van Horn (1975) ada 6 variabel yang mempengaruhi keberhasilan implementasi kebijakan yaitu (1) standar dan sasaran kebijakan; (2) sumberdaya; (3) hubungan antar organisasi; (4) karakteristik agen pelaksana; (5) disposisi implementor; (6) kondisi sosial, ekonomi, politik. Hasil dari penelitian ini berdasarkan dari 6 indikator diatas, bahwa program PTSL di Provinsi Jawa Timur sudah berjalan dengan cukup baik, tetapi masih terdapat beberapa hambatan seperti kurangnya pemahan masyarakat, perangkat desa serta kelompok masyarakat terkait pentingnya pendaftaran tanah dan masalah terkait syarat administratif untuk mengikuti program PTSL, serta terkait masalah PPh dan BPHTB yang nilainya terlalu besar bagi sebagian masyarakat. Saran yang dapat diberikan oleh peneliti ialah dengan meningkatkan koordinasi antara BPN dengan pihak-pihak yang terlibat dalam implementasi program PTSL, dan melakukan penyuluhan secara berkala kepada masyarakat, perangkat desa, serta kelompok masyarakat terkait pentingnya program PTSL, memberikan pelatihan terkait petunjuk dan teknis pelaksanaan program PTSL. Kata Kunci: Pembangunan nasional, Implementasi, Pendaftaran Tanah Sistematis Lengkap.